2017
DOI: 10.2147/jpr.s138360
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive tolerance to NSAIDs in the agranular insular cortex is mediated by opioid mechanism

Abstract: Several lines of investigations have shown that in some brain areas, in particular, in the midbrain periaqueductal gray matter, rostral ventromedial medulla, central nucleus of amygdala, nucleus raphe magnus, and dorsal hippocampus, microinjections of nonsteroidal anti-inflammatory drugs (NSAIDs) induce antinociception with distinct development of tolerance. The agranular insular cortex (AIC) is a small region of the cerebral cortex located on the lateral area of the rat’s cerebral hemisphere that is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The NAc is important in many functions (Floresco, 2015), such as learning and memory (Li et al, 2018), reward processing (Carlezon and Thomas, 2009), addiction behavior, locomotor activity, stress-related aversion, liking (Castro et al, 2016), motivation (Castro and Bruchas, 2019), and sexual motivation (Everitt, 1990;Beny-Shefer et al, 2017). In addition, NAc dysfunction is associated with many mental disorders, including schizophrenia (Cotter et al, 2001), Huntington's disease (Albin et al, 1989), alcohol addiction and drug abuse (Volkow et al, 2007;Lobo et al, 2010;Pirkulashvili et al, 2017;Morales et al, 2019), Alzheimer's disease (Schliebs and Arendt, 2011;Nie et al, 2017), and depression (Nestler and Carlezon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The NAc is important in many functions (Floresco, 2015), such as learning and memory (Li et al, 2018), reward processing (Carlezon and Thomas, 2009), addiction behavior, locomotor activity, stress-related aversion, liking (Castro et al, 2016), motivation (Castro and Bruchas, 2019), and sexual motivation (Everitt, 1990;Beny-Shefer et al, 2017). In addition, NAc dysfunction is associated with many mental disorders, including schizophrenia (Cotter et al, 2001), Huntington's disease (Albin et al, 1989), alcohol addiction and drug abuse (Volkow et al, 2007;Lobo et al, 2010;Pirkulashvili et al, 2017;Morales et al, 2019), Alzheimer's disease (Schliebs and Arendt, 2011;Nie et al, 2017), and depression (Nestler and Carlezon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that opioid receptor blockers injected into the core brain region of descending pain pathway could effectively reduce the analgesic effects of NSAIDs and have further suggested that NSAIDs act on the descending pain pathway via the endogenous opioid system to produce an antinociception effect. 36 , 37 , 38 Neuroimaging information may yield important representations in relation to treatment processes and outcomes. Although limited in number, some studies based on MRI techniques have revealed that changes in activity or morphology of the trigeminovascular system in patients with migraine were affected by different treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an effect of phenylbutazone after 29 days of administration in this study also suggests the development of drug tolerance. While this may not be well documented in horses, the development of anti-nociceptive tolerance to NSAIDs is documented in several species [48,49], and after 4 days of diclofenac, ketorolac, and lornoxicam administration in a rat nociceptive pain model [48]. Additionally, a recent meta-analysis of NSAIDs use by human knee OA patients revealed moderate pain reduction that peaked at 2 weeks, followed by diminished efficacy over 26 weeks [49].…”
Section: Discussionmentioning
confidence: 99%